The Effect of Sustainability Orientation and Marketing Orientation on Marketing Performance in SMEs - Tri Widayati; Nurchayati Nurchayati; Suparmi Suparmi; Sri Suprapti (Research Horizon, 2023)
The success of a company can be measured through its marketing performance. To achieve success in marketing, companies must adopt a strategic approach that suits dynamic market conditions and increasingly high demands from customers. To achieve this, companies must design the right strategic approach. Having a deep understanding of the factors that influence marketing performance is very important in achieving this goal. Sustainability orientation and marketing orientation have been recognized as key elements that can have a significant impact on a company's marketing success. This study aims to analyze the effect of sustainability orientation and marketing orientation on marketing performance. In combination, sustainability orientation and marketing orientation can give companies a significant advantage in achieving successful marketing performance. This research is a quantitative approach. The number of samples used in this study were 194 samples taken from Small and Medium Enterprises (SMEs) in Central Java Province as respondents in this study. The data source used is a questionnaire with a Likert scale of 1 to 5 points. Analysis test was carried out using SmartPLS software. The results of the research show that there is a significant influence between sustainability orientation and marketing orientation. In addition, the sustainability orientation also has a significant positive effect on marketing performance. Furthermore, this study found that marketing orientation also has a positive and significant influence on marketing performance. In addition, the marketing orientation variable also functions as a reliable mediating variable in mediating the relationship between sustainability orientation and marketing performance.